2015
DOI: 10.1111/1475-6773.12356
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Respondent Characteristics on the Validity of Self‐Reported Survey Responses

Abstract: Self-reported number of chronic conditions and prescription medications are not in high concordance with claims data. Health care researchers and policy makers using patient self-reported data should be aware of these potential biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A study determining the agreement between self-reported and diagnosis-based multimorbidity in older community dwelling women reported similar findings, where agreement was found to decrease with decreasing cognition and education, increasing age, and four or more diseases [ 22 ]. Multiple chronic conditions and polypharmacy have also been shown to negatively affect cognitive recall [ 55 ]. In addition, patients with chronic disease often experience co-morbidities such as mental health conditions and psychosocial difficulties (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A study determining the agreement between self-reported and diagnosis-based multimorbidity in older community dwelling women reported similar findings, where agreement was found to decrease with decreasing cognition and education, increasing age, and four or more diseases [ 22 ]. Multiple chronic conditions and polypharmacy have also been shown to negatively affect cognitive recall [ 55 ]. In addition, patients with chronic disease often experience co-morbidities such as mental health conditions and psychosocial difficulties (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We address two aspects of misclassification: self‐reported prescription drug use, and lack of specificity of prescription drug exposure. With respect to the former, misclassification is more likely to involve underreporting of prescription drug use overall, with evidence for underreporting of analgesics and sedatives, increased underreporting of all prescription drugs with increased age and number of dispensed prescriptions, but reduced underreporting with increased numbers of chronic conditions …”
Section: Discussionmentioning
confidence: 99%
“…With respect to the former, misclassification is more likely to involve underreporting of prescription drug use overall, with evidence for underreporting of analgesics and sedatives, 38 increased underreporting of all prescription drugs with increased age and number of dispensed prescriptions, but reduced underreporting with increased numbers of chronic conditions. 39 Lack of specificity of prescription drug exposures is implicit in the HRS questions about prescription drug use for pain or sleep. Multiple prescription and over-thecounter therapeutics are available to treat chronic pain and insomnia, 40,41 and we have no specific information (chemical entity, class, or brand) on primary (or concomitant) analgesic or sedative prescription (or over-the-counter) drugs from the core interview.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reporting by the elderly on prescription medications and chronic conditions has not been shown to align with medical claims data. 45 Unmeasured confounders may have been a factor in this study. The sample was not weighted to be representative of the US general population, and this study is limited due to the disproportionate subsamples by sex and race.…”
Section: Discussionmentioning
confidence: 90%